2015
DOI: 10.1038/ncomms8187
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic dynamics of synchronization in driven colloids

Abstract: Synchronization of coupled oscillators has been scrutinized for over three centuries, from Huygens' pendulum clocks to physiological rhythms. One such synchronization phenomenon, dynamic mode locking, occurs when naturally oscillating processes are driven by an externally imposed modulation. Typically only averaged or integrated properties are accessible, leaving underlying mechanisms unseen. Here, we visualize the microscopic dynamics underlying mode locking in a colloidal model system, by using particle traj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 57 publications
1
74
1
Order By: Relevance
“…The natural frequency of the particle driven over the optical potential energy landscape by the DC component of the driving force couples to the frequency of the AC component. As we have shown previously [53], this coupling leads to dynamic mode locking. This work considers the frequency and amplitude dependence of the synchronisation, through experiments, Langevin dynamics (LD) simulations and dynamic density functional theory (DDFT).…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…The natural frequency of the particle driven over the optical potential energy landscape by the DC component of the driving force couples to the frequency of the AC component. As we have shown previously [53], this coupling leads to dynamic mode locking. This work considers the frequency and amplitude dependence of the synchronisation, through experiments, Langevin dynamics (LD) simulations and dynamic density functional theory (DDFT).…”
Section: Introductionsupporting
confidence: 70%
“…Each colour and value of r represents a single mode locked velocity. The state diagram is formed from twisted 'Arnold Tongues' [1], where each separated region of the same colour actually represents a different dynamic mode with the same average velocity [53]. The second critical point of the 'zeroth' step appears as the effective critical driving velocity, F C,eff , below which the particle is pinned to the landscape and does not slide.…”
Section: The 'High Frequency' Theorymentioning
confidence: 99%
“…In the case of vortex motion in type-II superconductors, Martinoli et al reported the first observation of Shapiro steps for dc and ac driven vortices interacting with a periodic one-dimensional (1D) substrate created by periodic thickness modulations of the sample 14,15 , while similar effects were observed for vortices driven over 1D 16,17 or two-dimensional (2D) 18,19 periodic substrates. More recently, Shapiro steps have been found for ac and dc driven colloidal particles moving over a quasi-1D periodic substrate 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Other simulation work [26] addressed the case where the 2D sliding lattice and the periodic potential are fully matched, in addition to ratcheting conditions in mixtures. Very recently, the microscopic dynamics underlying mode locking in a colloidal model system has been recorded in a simple, yet noteworthy, 1D experimental setup [11]. In this work we study the feasibility of observing Shapiro steps under reasonably realistic conditions in 2D sliding colloid monolayers, under the wider range of conditions that can be realized experimentally.…”
Section: Introductionmentioning
confidence: 99%